2004
DOI: 10.1160/th04-02-0095
|View full text |Cite
|
Sign up to set email alerts
|

CD14+CD16+ monocytes in coronary artery disease and their relationship to serum TNF-α levels

Abstract: Monocytes play a central role in the inflammatory disease atherosclerosis. CD14+CD16+ monocytes are considered proinflammatory monocytes, as they have an increased capacity to produce proinflammatory cytokines, such as TNF-alpha, and are elevated in various inflammatory diseases. We hypothesized that patients with coronary artery disease (CAD) have increased levels of CD14+CD16+ monocytes, and that CD14+CD16+ monocytes are associated with inflammation markers. We investigated CD14+CD16+ monocytes in 247 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(117 citation statements)
references
References 28 publications
6
111
0
Order By: Relevance
“…Recent analysis using intracellular staining confirmed that CD14 ϩ CD16 ϩ monocytes are major producers of TNF-␣ and possess a higher sensitivity for LPS-induced TNF-␣ production in vivo compared with CD14 ϩϩ CD16 Ϫ monocytes (6,62,64). Therefore, it seems plausible that CD14 ϩ CD16 ϩ monocytes are responding to mild endotoxemia accompanying strenuous exercise (9,50) or EHS (68).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent analysis using intracellular staining confirmed that CD14 ϩ CD16 ϩ monocytes are major producers of TNF-␣ and possess a higher sensitivity for LPS-induced TNF-␣ production in vivo compared with CD14 ϩϩ CD16 Ϫ monocytes (6,62,64). Therefore, it seems plausible that CD14 ϩ CD16 ϩ monocytes are responding to mild endotoxemia accompanying strenuous exercise (9,50) or EHS (68).…”
Section: Discussionmentioning
confidence: 99%
“…NF-B DNA binding in the liver (11) and intestinal epithelial/mucosal cells (56) is an important source of inflammatory mediators during endotoxemia (11,57) before spillover into the systemic circulation (28). It is possible, however, given the findings by Belge et al (6) and others (62,64) regarding CD14 ϩ CD16 ϩ capacity for LPS-induced TNF-␣ production in vivo, that circulating inflammatory monocytes may be contributing to the changes in circulating cytokine profiles observed during EHS (68).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CD16? monocytes were seen in the patient cohort [26]. A recent study analyzing coronary artery calcium (CAC) and inflammatory markers found that higher frequencies of CD16?…”
Section: Pathophysiology Of Coronary Artery Disease In Patients With mentioning
confidence: 97%
“…Using flow cytometry, the number of circulating CD14 + CD16 ++ monocytes has been shown to be inversely related to plasma HDL levels, and CD16 + monocytes are proportional to the severity of atherosclerosis 142 , whereas a reduction in the monocyte subpopulation is associated with a reduction in intima-media thickness 143 . Again, these measures do not provide any information about to the underlying pathogenesis of disease.…”
Section: Molecular Techniques-mentioning
confidence: 99%